Assessing the Potential of Decentralized Solar Energy for Livelihood Creation and Reducing Migration (Indian Journal of Extension Education, 2014)
Limited availability of energy in rural areas hampers irrigation and obstructs creation of other livelihood opportunities that forces people to migrate. One of the solutions to the problem is utilization of decentralized solar photovoltaic and solar thermal technologies to create livelihood opportunities along with provision for irrigation. The recent examples of public private partnership in Bihar for deployment of solar pumps have enabled irrigation, despite rising diesel prices and limited power availability for few hours in a week. The solar panels generate electricity that can be used directly to operate irrigation pumps or can be used for charging batteries. Solar lamps and other livelihood creating equipments can be operated using the batteries charged. Solar thermal applications in dairy and agro-processing industries can create livelihood opportunities. The innovation or uniqueness in the approach proposed in this paper is of implementing community owned solar photovoltaic or solar thermal technologies. Sharing of the equipments by different users will enhance the economic viability of these technologies. Solar pumps will help farmers to irrigate land and earn livelihood from agriculture while charged batteries can provide energy for micro-enterprises. Solar thermal technologies can enable livelihood creation by enabling farmers to process agricultural produce in rural areas. Solar powered milk processing units can also generate employment.